2016
DOI: 10.1186/s12906-016-1283-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Vaccinium uliginosum extract on tablet computer-induced asthenopia: randomized placebo-controlled study

Abstract: BackgroundTo investigate the alleviation effect of Vaccinium uliginosum extract (DA9301) on tablet computer-induced asthenopia.MethodsThis was a randomized, placebo-controlled, double-blind and parallel study (Trial registration number: 2013–95). A total 60 volunteers were randomized into DA9301 (n = 30) and control (n = 30) groups. The DA9301 group received DA9301 oral pill (1000 mg/day) for 4 weeks and the control group received placebo. Asthenopia was evaluated by administering a questionnaire containing 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 36 publications
0
28
0
1
Order By: Relevance
“…Bhargava et al observed that, after 45 days of omega‐3 fatty acid treatment, patients demonstrated a significant improvement in dry eye symptoms and tear break‐up time. Similarly, Park et al found that a four‐week treatment with blueberry extract (species: Vaccinium uliginosum ) significantly reduced overall subjective eye strain symptoms.…”
Section: Management Of Digital Eye Strainmentioning
confidence: 92%
See 1 more Smart Citation
“…Bhargava et al observed that, after 45 days of omega‐3 fatty acid treatment, patients demonstrated a significant improvement in dry eye symptoms and tear break‐up time. Similarly, Park et al found that a four‐week treatment with blueberry extract (species: Vaccinium uliginosum ) significantly reduced overall subjective eye strain symptoms.…”
Section: Management Of Digital Eye Strainmentioning
confidence: 92%
“…Lubricating eye drops seem to help relieve (although not eliminate) symptoms of dryness, tiredness and difficulty focusing . Other treatment options are a dietary supplement of either omega‐3 fatty acids or blueberry extract . Bhargava et al observed that, after 45 days of omega‐3 fatty acid treatment, patients demonstrated a significant improvement in dry eye symptoms and tear break‐up time.…”
Section: Management Of Digital Eye Strainmentioning
confidence: 99%
“…Asthenopia, or eye strain, describes nonspecific symptoms that occur after extended use of the eyes. 11 Common causes include prolonged reading or computer use, inadequate or excessive lighting, dry eye, presbyopia, and uncorrected refractive errors. 11 Use of computers, tablets, and mobile devices has become essential in everyday work, study, and leisure activities.…”
Section: Cephalgia From Asthenopiamentioning
confidence: 99%
“…11 Common causes include prolonged reading or computer use, inadequate or excessive lighting, dry eye, presbyopia, and uncorrected refractive errors. 11 Use of computers, tablets, and mobile devices has become essential in everyday work, study, and leisure activities. 12 Continuous attention to these screens is closely related to a decreased blink rate and increased accommodation and convergence, which leads to eye dryness and asthenopia.…”
Section: Cephalgia From Asthenopiamentioning
confidence: 99%
“…Some studies have reported that certain natural plant-derived extracts, including bilberry, Haematococcus pluvialis, blackcurrant, and black soybean hull extracts, can ameliorate visual fatigue and exert antioxidant effects [2,7,9]. Antioxidant compounds have Been shown to be effective in improving visual function [7,10].…”
Section: Introductionmentioning
confidence: 99%